Ankylosing Spondylitis: A Trade Off of HLA-B27, ERAP, and Pathogen Interconnections? Focus on Sardinia - Paladini, Fabiana; Fiorillo, Maria Teresa; Tedeschi, Valentina; Cauli, Alberto; Mathieu, Alessandro; Sorrentino, Rosa (Frontiers in Immunology, 2019)
Abstract The frequency of HLA-B27 in patients with Ankylosing Spondylitis (AS) is over 85%. There are more than 170 recognized HLA-B27 alleles but the majority of them is not sufficiently represented for disease-association studies. So far only two alleles, the HLA-B*2706 in Asia and the HLA-B*2709 in Sardinia, have not been found to confer susceptibility to AS. The highly homogenous genetic structure of the Sardinian population has favoured the search of relevant variants for such studies. Moreover, malaria, once endemic in the island, has been shown to have contributed to shape the genome of the native population affecting the frequency of relevant alleles. In Sardinia, the prevalence of HLA-B*2709, which differs from the strongly AS-associated B*2705 prototype for one amino acid (His/Asp116) in the F pocket of the peptide binding groove, is around 20% of all HLA-B27 alleles. We have previously hypothesized that malaria could have contributed to the establishment of this allele in Sardinia. Based on our recent findings, in this perspective article we speculate that the Endoplasmic Reticulum AminoPeptidases, ERAP1 and 2, associated with AS and involved in antigen presentation, underwent co-selection by malaria. These genes, besides shaping the immunopeptidome of HLA-class I molecules, have other biological functions that could also be involved in the immunosurveillance against malaria.